Pacing strategy in long distance cross-country skiing. A study looking at female and male cross-country skiers at different performance level and how the track topography may influence their pacing strategy. - Bjørkesett, E. (The Arctic University of Norway, 2019)
The pacing strategy applied by athletes has significant effect on their performance in endurance sports. Although several studies have investigated pacing in different endurance sports, little information is known about pacing strategies in long distance cross-country (XC) skiing, for both sexes. This master thesis presents a novel approach to investigate what kind of pacing strategy elite and non-elite skiers perform during a long distance XC skiing race, and if different terrain will influence their pacing strategy. We`ve estimated the skiers lap times on every passed 10 km, uphill and downhill terrain. Method: On the same day 100 XC skiers (50 female and 50 male skiers) completed an individual time trial in a Norwegian national championship, of long distance. Female XC skiers completed a 30 km race, while male XC skiers completed a 50 km in free technique. The trial was 10 km long. Emit Time Station ETS1 recorder split times of number of laps, time used in one chosen uphill terrain and one downhill terrain. Results: Independent of performance level, both groups of female and male XC skiers decrease in average lap times in all measured distances (10 km lap, uphill and downhill terrain) with strong statistical significant p<0.01. Female and male elite group (EG) adopt a more even positive pacing strategy, than female and male non-elite group (NEG). Conclusion: The main findings of the current study were (I) XC skiers employ a general positive pacing on a lap-to-lap basis, independent on terrain, sex and performance level. (II) Non-elite skiers tend to have a fast start with difficulty to optimize even pacing strategy and significant fall in performance. (III) Pacing strategy in uphill terrain reflects overall pacing strategy of the performance.